2014
DOI: 10.1007/s11295-014-0769-2
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity in peach [Prunus persica (L.) Batsch] at the University of Florida: past, present and future

Abstract: The University of Florida (UF) stone fruit breeding and genetics program was created in 1952 to develop early ripening stone fruit cultivars with high quality, adaptation to summer rainfall, low chilling requirements, and the ability to withstand high disease pressure. Diverse germplasm sources were used to introduce desirable traits in UF breeding pool. The main objective of this research was to determine the genetic diversity and population structure of the breeding germplasm, and to search for loci under se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
8
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 70 publications
3
8
3
Order By: Relevance
“…Similar results associating genetic structure with fruit characteristics were also reported before by other authors LI et al, 2013;CHAVEZ et al, 2014) analyzing peach germplasm. Aranzana et al (2010) identified three main groups: melting flesh peaches, melting flesh nectarines, and non-melting cultivars.…”
Section: Delta K (δK) Values Using the Evanno Methods (Evanno Et Al supporting
confidence: 90%
See 3 more Smart Citations
“…Similar results associating genetic structure with fruit characteristics were also reported before by other authors LI et al, 2013;CHAVEZ et al, 2014) analyzing peach germplasm. Aranzana et al (2010) identified three main groups: melting flesh peaches, melting flesh nectarines, and non-melting cultivars.…”
Section: Delta K (δK) Values Using the Evanno Methods (Evanno Et Al supporting
confidence: 90%
“…An average of 8.0 alleles per locus was observed, which is higher than the values reported in previous studies on genetic diversity in peach Chavez et al (2014) reported that a total of 237 alleles were amplified for 168 peach and nectarine cultivars and selections of the University of Florida (UF) peach germplasm using 36 SSR markers. Comparing three SSR markers (BPPCT014, BPPCT017 and CPPCT022) in common with their work, we were able to distinguish an average of 24 genotypes per marker while only 16 genotypes per marker were observed in UF peach germplasm.…”
Section: Genetic Diversity Analysiscontrasting
confidence: 64%
See 2 more Smart Citations
“…In peach, availability of different molecular markers allowed to gain information on some 760 Quantitative Trait Loci and Mendelian Trait Loci linked to horticultural and physiological traits such as tree development, pest and disease resistance, flowering, ripening, seed and fruit quality [16] [17].…”
mentioning
confidence: 99%